2008
DOI: 10.1007/s11947-008-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sonication and Edible Coating Containing Rosemary and Tea Extracts on Reduction of Peanut Lipid Oxidative Rancidity

Abstract: Rancidity due to the lipid oxidation process is a critical factor influencing the quality of roasted peanuts. Sonication in combination with edible coatings added with plant extracts may extend the oxidative stability of peanuts. Peanuts were roasted at 178°C for 15 min, subjected to sonication in hexane for 10 min, and then coated with carboxymethyl cellulose (CMC) solution mixed with rosemary, tea extracts, and α-tocopherol and stored at 35°C for 12 weeks. The oxidative stability of the samples was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…The effectiveness of coating with tocopherol is highly dependent on the concentration and temperature (Tasan & Demirci, 2005). Similar, pro-oxidant effect of alpha tocopherol has been reported in peanut as well (Wambura et al, 2010;Wambura, Yang, & Mwakatage, 2011).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The effectiveness of coating with tocopherol is highly dependent on the concentration and temperature (Tasan & Demirci, 2005). Similar, pro-oxidant effect of alpha tocopherol has been reported in peanut as well (Wambura et al, 2010;Wambura, Yang, & Mwakatage, 2011).…”
Section: Resultssupporting
confidence: 65%
“…The role of phenolic compounds has been reported to improve the oxidation retardation capabilities of edible coatings (Mestrallet, Nepote, Quiroga, & Grosso, 2009;Wambura et al, 2010Wambura et al, , 2011. It is therefore, most likely that the effectiveness of methanolic extract of Cordia is due to these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The WVP of films was determined to be 0.232×10 −10 -1.160×10 −10 g/ms Pa, σ r took values between 17 and 44 N/mm 2 and ε r between 14% and 97%, Moreira et al (2009) analyzed the effect of a CMC coating during drying process on the quality of butternut squash slices and observed a slight improvement in weight loss and ascorbic acid retention in comparison with control samples without any coating. In addition, Wambura et al (2008) analyzed the effects of a CMC-based edible coating containing rosemary and tea extracts on the reduction of lipid oxidative rancidity. Reduction in oxidation of 66.1% and 10.4% was observed for samples roasted and coated with CMC films formulated with extracts of rosemary and tea, respectively, as compared to uncoated sample.…”
Section: Cellulose and Derivativesmentioning
confidence: 99%
“…Edible coatings prevent moisture loss and reduce oxygen diffusion in nuts (Quezada-Gallo 2009). Carboxymethyl cellulose (CMC; Wambura et al 2008Wambura et al , 2010Wambura et al , 2011, whey protein isolate (WPI; Mate et al 1996;Min and Krochta 2007;Han et al 2008) and corn zein (Wambura et al 2008) have been reported as coatings to retard the oxidative rancidity in peanuts. Carboxymethyl cellulose (CMC; Wambura et al 2008Wambura et al , 2010Wambura et al , 2011, whey protein isolate (WPI; Mate et al 1996;Min and Krochta 2007;Han et al 2008) and corn zein (Wambura et al 2008) have been reported as coatings to retard the oxidative rancidity in peanuts.…”
Section: Introductionmentioning
confidence: 99%